Interferensi Leksikal Kosakata Ragam Bahasa Takresmi ke dalam Ragam Bahasa Resmi dalam Bahasa Indonesia - Mujid Farihul Amin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Lexical interference is the entry of vocabulary from certain languages / languages into other languages / languages. In the use of official Indonesian languages, often people also use vocabulary commonly used in informal languages, such as kayak, bilang, bikin, cuman, cewek, nggak, dikasih, gitu, and gini. Good and right Indonesian should avoid things like that.